Production of Biodiesel from Sunflower Oil using Base Catalysts - Kinia Eldwita; Vivi Octhaviana; Rusdianasari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The reduction of petroleum reserves is a severe problem faced by many countries. With the help of the rapid development of science and technology, vegetable oil can not only be consumed but can also be processed into something that has more value, one of which is biodiesel. Biodiesel is a clean renewable fuel and can be used as the best substitute for diesel fuel. The purpose of this study is to provide a comprehensive overview of the development of research related to the production of biodiesel from sunflower oil using base catalysts. This research was conducted using the transesterification reaction method with the help of catalysts. Then the biodiesel yield from sunflower oil can be influenced by several factors, including the amount of catalyst, reaction temperature, reaction time, stirring speed, and molar ratio between methanol and oil. Based on the research, several tests were carried out. The first test was based on the influence of stirring speed, the results showed that the faster the stirring, the more biodiesel yield. The second test was based on the effect of reaction time; the results indicated that the reaction time could not significantly increase the biodiesel yield. The third test was based on the effect of the molar ratio of methanol and oil, the results showed that the optimum ratio could help drive the transesterification reaction towards the product. The fourth test looked at how the concentration of KOH solution affects the amount of biodiesel produced; the results showed that using the best amount of catalyst can make the transesterification reaction work better. The fifth test was based on the effect of reaction temperature; the results showed that at high temperatures (60°C) methanol mixes more easily with oil so that the biodiesel formation reaction takes place faster. From the results of this study, it can be concluded that sunflower oil can be used as one of the ingredients in making biodiesel.Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action